Classic and romantic German aesthetics - Bernstein, J. M. (Cambridge texts in the history of philosophy., 2003)
This volume includes the first translation into English of Schiller's Kallias Letters and Moritz's On the Artistic Imitation of the Beautiful, and new translations of some of Hölderlin's most important theoretical writings and works by Hamann, Lessing, Novalis and Schlegel.